Growth and Neurodevelopmental Outcomes of Very Low Birth Weight Infants upto Six Months of Age at a Tertiary Level NICU in Central India: A Prospective Cohort Study - KP Malini; Avyakt Aggarwal; Lalit M Malviya; Vidya Kumari Saurabh (JCDR Research and Publications Pvt. Ltd., 2023)
Introduction: The long-term outcomes of Very Low Birth Weight (VLBW) infants are influenced by prematurity, as well as the occurrence of various short-term morbidities, such as Respiratory Distress Syndrome (RDS), sepsis, Necrotising Enterocolitis (NEC), Patent Ductus Arteriosus (PDA), Intraventricular Haemorrhage (IVH), Periventricular Leukomalacia (PVL), Retinopathy Of Prematurity (ROP), and Chronic Lung Disease (CLD). It has been estimated that approximately half of all VLBW infants develop cognitive and behavioural deficits in the future. Therefore, studying VLBW infants and providing longitudinal follow-up after their hospital discharge is increasingly important. This helps in the early diagnosis of neurodevelopmental abnormalities and enables timely intervention for a better quality of life in the future. Aim: To assess the growth and neurodevelopmental outcomes of VLBW infants discharged from the NICU until six months of age. Materials and Methods: A prospective cohort study was conducted in the Neonatal In tensive Crae Unit (NICU) at NSCB Medical College, Jabalpur, Madhya Pradesh, India. The duration of the study was one year and six months, from March 2018 to September 2019. A total of 40 VLBW infants were enrolled and followed-up for six months. The infants were divided into two groups: Group 1 (<32 weeks) and group 2 (>32 weeks). Physical parameters such as weight, length, and head circumference were recorded on admission and at one, three and six months of corrected gestational age. Developmental assessment was performed using the Denver Developmental Screening Test-II (DDST-II) method. The association of risk factors with neurodevelopmental outcomes was also assessed. Data were analysed using Statistical Package for Social Sciences (SPSS) version 20.0, and the Chi-square test, Fisher's-exact test, and Student's t-test were used. A p-value less than 0.05 was considered significant. Results: Among the 40 subjects, 12 (30%) were <32 weeks, and 28 (70%) were ≥32 weeks. Overall, parameters were higher in infants ≥32 weeks. Weight and head circumference gain velocity were greater in infants ≥32 weeks during the first three months of life (p<0.05). From three to six months, <32 weeks infants showed a significant increase (p<0.001) in weight and head circumference gain velocity. The length gain velocity in both groups was comparable since birth, and <32 weeks VLBW infants demonstrated good catch-up growth, which was statistically significant (p<0.05). At six months of corrected age, 16 (40%) infants out of the total 40 infants had abnormal neurodevelopmental outcomes. A total of 7 (58.33%) of the <32 weeks VLBW infants and 9 (32.14%) of the ≥32 weeks VLBW infants had Neurodevelopmental Delay (NDD). Hypoglycaemia, shock, hyaline membrane disease, and mechanical ventilation were significantly associated with an increased risk of NDD. Conclusion: The incidence of NDD was significantly higher in infants with lower gestational age, lower birth weight and the presence of associated factors such as hyaline membrane disease, hypoglycaemia, shock, ventilation, and hyperbilirubinaemia. Improved perinatal care, early assessment of development using appropriate tools, and early intervention are necessary to improve the outcomes of these infants.